Artificial Intelligence as Wasilah of Digital Khidmah: Nahdlatul Ulama Actors' Responses to Da'wah and Literacy - Wahyu Khoiruzzaman; Ilmi Hidayati (Journal of Nahdlatul Ulama Studies, 2026)
The rapid development of Artificial Intelligence (AI), especially generative AI and large language models (LLMs), has transformed the ways people search for, produce, and circulate religious knowledge. In the context of Nahdlatul Ulama (NU), AI offers opportunities for strengthening digital da'wah, religious literacy, and organizational services, yet it also raises serious questions about epistemic validity, religious authority, and the continuity of sanad in Islamic learning. This article analyzes how NU actors respond to AI in relation to da'wah, religious literacy, and digital khidmah. It employs a descriptive qualitative and exploratory approach based on literature review, digital observation, and limited interviews with NU actors concerned with media and digital transformation. The data were analyzed thematically by focusing on three issues: AI as a tool for digital service, the epistemic risks of AI-generated religious answers, and the ethical importance of sanad, tabayyun, and human authority. The article argues that AI should be positioned as a wasilah for digital khidmah, rather than a substitute for ulama, kiai, pesantren, or bahtsul masail. Its contribution lies in formulating an NU-based ethical reading of AI that combines technological adaptation with the preservation of religious knowledge, scholarly authority, source credibility, and pesantren-based ethics.